Ceramic component

By introducing a zirconium atom layer at the grain boundaries of alumina and tungsten carbide, the problems of porosity formation and insufficient sealing strength of ceramic components under high temperature conditions are solved, achieving excellent ductility and bending strength at high temperatures, making it suitable for components in high-temperature environments such as gas turbines and satellite jet nozzles.

CN121079283APending Publication Date: 2025-12-05NITERRA CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480024993.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2024-11-08
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

The properties of existing ceramic components containing alumina and tungsten carbide need further improvement at high temperatures, especially at temperatures above 1400℃, where there are problems with pore formation and insufficient sealing strength.

Method used

A zirconium atomic layer is introduced at the grain boundary between alumina and tungsten carbide to control the porosity to below 0.3%, and the zirconium layer is formed according to the (100) plane arrangement period of tungsten carbide grains. Ceramic parts are prepared by hot pressing sintering.

Benefits of technology

It improves the ductility and bending strength of ceramic components under high temperature conditions, reduces porosity formation and sealing strength, and enables stable use at temperatures above 1400℃.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121079283A_ABST
    Figure CN121079283A_ABST
Patent Text Reader

Abstract

The ceramic member contains aluminum oxide (Al2O3) and tungsten carbide (WC). In this ceramic member, an atomic layer formed of zirconium (Zr) is present at the grain boundary between the grains of alumina and the grains of tungsten carbide. The ratio of pores in any cross section of the ceramic member is 0.3% or less.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a ceramic member. BACKGROUND

[0002] A technique is disclosed which, in order to improve the properties of a ceramic member having alumina (Al2O3) as a main component, causes the ceramic member to contain tungsten carbide (WC) in addition to alumina (Al2O3).

[0003] For example, Patent Literature 1 discloses a ceramic member characterized by containing alumina (Al2O3) and tungsten carbide (WC), and an atomic layer formed of at least one element selected from transition metals belonging to Groups 4 to 6 of the periodic table, yttrium (Y), scandium (Sc), and lanthanoid elements being present at the grain boundaries of alumina (Al2O3) grains and tungsten carbide (WC) grains.

[0004] PRIOR ART DOCUMENTS

[0005] PATENT LITERATURE

[0006] Patent Literature 1: Japanese Patent No. 6491363 SUMMARY

[0007] PROBLEMS TO BE SOLVED BY THE INVENTION

[0008] As described above, in order to improve the properties of a ceramic member containing alumina (Al2O3) and tungsten carbide (WC), various methods have been proposed.

[0009] An object of one aspect of the present application is to further improve the properties of a ceramic member containing alumina and tungsten carbide under a high-temperature environment.

[0010] SOLUTION TO PROBLEM

[0011] [1]

[0012] One aspect of the present application relates to a ceramic member containing alumina (Al2O3) and tungsten carbide (WC), in which an atomic layer formed of zirconium (Zr) is present at the grain boundaries of alumina (Al2O3) grains and tungsten carbide (WC) grains, and the ratio of pores in any one cross section of the ceramic member is 0.3% or less.

[0013] [2]

[0014] In the ceramic member according to the aspect of the present application described in [1], the atomic layer can be formed at the grain boundaries in accordance with the arrangement period of at least either of the alumina (Al2O3) grains and the tungsten carbide (WC) grains.

[0015] [3]

[0016] In the ceramic member according to the aspect of the present application described in [2], the atomic layer can be formed at the grain boundary in accordance with the arrangement period of the (100) plane of the grains of tungsten carbide (WC).

[0017] [4]

[0018] In the ceramic member according to the aspect of the present application described in [3], the atomic layer can be formed at the grain boundary in a thickness of 1 arrangement amount of the (100) plane of the grains of tungsten carbide (WC).

[0019] [5]

[0020] The ceramic member according to the aspect of the present application described in any one of [1] to [4] can be used in a high-temperature environment of 1400°C or higher.

[0021] [6]

[0022] The ceramic member according to the aspect of the present application described in any one of [1] to [5] can also be used for any one of a member for a gas turbine, an ejection nozzle for an artificial satellite, a mold for a lens, a member for an aircraft engine, and a sealing material.

[0023] Effects of the Invention

[0024] According to the aspect of the present application, a ceramic member having improved ductility and bending strength characteristics in a high-temperature environment can be obtained. BRIEF DESCRIPTION OF DRAWINGS

[0025] Figure 1 A perspective view showing the appearance of the ceramic member according to an embodiment.

[0026] Figure 2 A diagram showing a TEM image at the A-A cross section of the ceramic member according to an embodiment.

[0027] Figure 3 A diagram showing a HAADF-STEM image near the grain boundary of the ceramic member according to an embodiment.

[0028] Figure 4 A diagram in which each component is color-divided in a SEM image of one cross section of the ceramic member according to an embodiment and is shown.

[0029] Figure 5 A diagram showing a TEM image at one cross section of the ceramic member after stress application.

[0030] Figure 6 A flowchart showing the flow of the manufacturing method of the ceramic member according to an embodiment. DETAILED DESCRIPTION

[0031] Hereinafter, an embodiment of the present application will be described with reference to the drawings. In the present embodiment, a ceramic member 10 as one example of a ceramic member will be described. The ceramic member 10 is suitable for use as a ceramic member contained in a device used in a high-temperature environment of 1400°C or higher. Specifically, the ceramic member 10 is used, for example, in any one of a gas turbine member, a satellite ejection nozzle, a lens mold, an aircraft engine member, and a sealing material.

[0032] (Structure of Ceramic Member)

[0033] Figure 1 A perspective view showing the appearance of the ceramic member 10 is shown in FIG. 1. The ceramic member 10 contains alumina (AI2O3) and tungsten carbide (WC). In the ceramic member 10, an atomic layer formed of zirconium (Zr) exists at the grain boundary between the grains of alumina (AI2O3) and the grains of tungsten carbide (WC).

[0034] The atomic layer formed of zirconium (Zr) is obtained, for example, by adding zirconium oxide (ZrO2) or the like as a raw material at the time of manufacturing the ceramic member 10.

[0035] An example of a TEM image of the ceramic member 10 shown in FIG. 2 is shown in FIG. 3. Figure 2 An example of a TEM image of the ceramic member 10 shown in FIG. 2 is shown in FIG. 3. Figure 1 An example of a TEM image of the ceramic member 10 shown in FIG. 2 is shown in FIG. 3. Figure 2 The TEM image shown in FIG. 3 can be obtained by observing a sample prepared according to the following procedure with a transmission electron microscope.

[0036] First, the ceramic composition is processed into a φ3 mm disc-shaped plate of a prescribed position and direction using a diamond cutter and an ultrasonic disc cutter, and the thickness is adjusted and thinned to less than 100 μm using 30 μm diamond polishing paper. Next, dimpling is performed in the center of the disc using a dimpler, and processing is performed using a precision ion polishing system (PIPS). Figure 2 The TEM image shown in FIG. 3 is an image obtained by observing a sample obtained by setting the ion milling conditions to Ar ions, an acceleration voltage of 4.0 kV, a beam irradiation angle of ±4°, and performing damage layer removal processing at 1.0 kV for 2 minutes after the sample was perforated.

[0037] An example of a TEM image of the ceramic member 10 shown in FIG. 2 is shown in FIG. 3. Figure 3 An example of a TEM image of the ceramic member 10 shown in FIG. 2 is shown in FIG. 3. Figure 1An example of a HAADF-STEM image near the grain boundaries of the ceramic component 10 is shown. HAADF-STEM (High-Angle Annular Dark Field Scanning Transmission Electron Microscopy) is a high-angle scattering annular dark field scanning transmission microscopy. In the HAADF-STEM image, heavier elements are shown brightly. Compared with the structural model, the bright white spots correspond to atomic pillars of tungsten (W).

[0038] Figure 3 HAADF-STEM images showing the area near the grain boundaries between alumina and tungsten carbide grains. Figure 3 In this process, the atomic layer of the alumina grains is designated as the alumina layer 20, the atomic layer of the tungsten carbide grains is designated as the WC layer 30, and the atomic layer from the zirconium compound is designated as the Zr layer 40.

[0039] like Figure 3 As shown, in the ceramic component 10, a Zr layer 40 exists between the alumina layer 20 and the WC layer 30. In other words, in the ceramic component 10, there is an atomic layer formed of zirconium (Zr) at the grain boundaries between the alumina (Al2O3) grains and the tungsten carbide (WC) grains. Furthermore, the Zr layer 40 contains a segregated layer of zirconium atoms (a single layer of zirconium atoms arranged in a single layer).

[0040] The Zr layer 40 is formed at the grain boundaries according to the arrangement period of at least one of the alumina grains and the tungsten carbide grains. More specifically, the Zr layer 40 is formed according to the atomic arrangement of the WC layer 30. That is, the Zr layer 40 is formed at the grain boundaries according to the arrangement period of the (100) face of the tungsten carbide (WC) grains.

[0041] And, as Figure 3 As shown, the Zr layer 40 is preferably formed at the grain boundaries with a thickness of 1 arrangement of the (100) planes of tungsten carbide (WC) grains.

[0042] As described above, the bonding strength between the alumina grains and the tungsten carbide grains can be improved by having a Zr layer 40 at the grain boundaries between the alumina grains and the tungsten carbide grains.

[0043] Furthermore, in the ceramic component according to this embodiment, the porosity ratio in any cross-section is 0.3% or less. Therefore, a ceramic component with excellent ductility can be obtained under high-temperature conditions (e.g., above 1400°C).

[0044] (Regarding pores in ceramic components)

[0045] Next, the pores contained in the ceramic member 10 are described in more detail. The pores refer to voids contained in the solid ceramic member 10. In addition, the pores contained in the ceramic member obtained after the ceramic member 10 is molded and processed are also referred to as cavities.

[0046] For example, when the ceramic member is placed in a high-temperature environment of 1400°C or higher and a stress application environment, the ratio of the pores or cavities contained in the structure of the ceramic member tends to increase. The ratio tends to increase over time.

[0047] It is known that the destruction of the ceramic member in a high-temperature environment is caused by the generation, growth, and connection of pores or cavities in the ceramic member. In addition, in a ceramic member that is processed into a prescribed shape, by applying stress such as bending processing to the ceramic member, the ratio of the pores or cavities tends to increase.

[0048] Therefore, by reducing the ratio of the pores contained in the ceramic member as much as possible, a ceramic member with higher performance (specifically, a ceramic member excellent in high-temperature ductility) can be expected.

[0049] In the ceramic member 10 related to the present embodiment, the ratio of the pores in any one cross section is 0.3% or less. Thereby, a ceramic member excellent in high-temperature ductility can be obtained. Note that the ceramic member 10 having such a property can be manufactured by the method described later.

[0050] The determination of the ratio of the pores can be performed by extracting a plurality of samples from the target ceramic member and calculating the pores of each sample according to the pore measurement method described later. Also, in a case where the ratio of the pores in the sample having the largest ratio of the pores among the plurality of samples is 0.3% or less, it can be determined that the ratio of the pores is 0.3% or less.

[0051] In the ceramic member 10 related to the present embodiment, the lower limit value of the ratio of the pores is not particularly limited. In a conventional ceramic member containing alumina and tungsten carbide, it is difficult to make the pores zero (absence of pores). Therefore, the ratio of the pores in the ceramic member 10 related to the present embodiment is greater than 0%.

[0052] In the ceramic member 10 related to the present embodiment, even after stress is applied (for example, bending processing or the like), the increase in the ratio of the pores can be suppressed to some extent (see Figure 5 ). The results of observing one cross section of the ceramic member 10 after stress is applied (after the bending test) in the present example are shown in Figure 5 .

[0053] (Measurement method of the ratio of the pores)

[0054] Here, one example of a method for measuring the ratio of the pores contained in the ceramic member 10 will be described.

[0055] First, after the solid ceramic member 10 is miniaturized, an arbitrary cross section is polished to the order of several micrometers. Next, by using a cross-sectional vertical ion milling method using a shadow mask, an ion-milled cross section in which the polishing damage is removed is formed by processing 50 μm or more in the depth direction from the polished surface, and is used as an observation surface. As a processing device, for example, an Ar ion milling device with an acceleration of 5 to 6 kV is used. As the observation surface, an area of 300 μm x 300 μm or more is ensured.

[0056] Next, an SEM image of the observation surface is taken. For example, using an electron microscope capable of being variable within 0.1 kV to 20 kV, the observation surface is imaged to obtain image data. For the obtained image data, the resolution and the magnification are adjusted so that a resolution (number of pixels) of 10 times or more of the smallest particles in the ceramic structure is achieved, and is saved in a data form without irreversible processing (for example, tiff or bmp).

[0057] Then, the obtained image data is subjected to image analysis. Specifically, using the region division function of an image analysis software (for example, Avizo software for material research (Thermo Fisher Scientific Inc.) or the like), the obtained image data is 3-valued. Specifically, the following 3 regions are each subjected to 3-valuing.

[0058] A: a region formed of alumina (AI2O3)

[0059] B: a region formed of tungsten carbide (WC)

[0060] C: a region of pores

[0061] When the above 3-valuing is performed, regardless of the isomorphic system or other crystal systems, the grain boundary layer is not considered. In the case of the isomorphic system, it is extracted in the form of a continuous region. Note that attention is paid to the fact that the SEM image has residual information in the depth direction, and the region division is performed using the information of the most surface. The numerical value is calculated using the pixel interval and the two-dimensional calculation function of the software, and the area and the occupancy ratio of each region are calculated.

[0062] Figure 4 One example of an image after 3-valuing processing of an SEM image of an arbitrary cross section of the ceramic member 10 using the above method is shown. In Figure 4 images of three samples (samples 1 to 3) extracted from one ceramic member 10 are shown. In addition, in Figure 4 the lower part of the image, the results of calculating the area ratio of each of the above A to C regions are shown.

[0063] AsFigure 4 In the ceramic member 10 according to the present embodiment, the ratio of the pores in any one cross section was confirmed to be 0.3% or less. In addition, the average value of the ratio of the pores was confirmed to be 0.2%.

[0064] Note that the method of measuring the ratio of the pores described above can also be used to calculate the proportions (volume%) of the alumina component and the tungsten carbide component contained in the ceramic member 10.

[0065] Specifically, in the image data in which the three regions A to C described above are individually three-valued, the areas of the respective regions are calculated. Then, based on the calculated values, A / (A+B+C) and B / (A+B+C) are calculated.

[0066] Thus, the proportions (volume%) of the respective components in the ceramic member 10 can be obtained. In Figure 4 the proportions of the alumina (AI2O3) component and the tungsten carbide (WC) component contained in the ceramic member 10 are shown. Note that the zirconium (Zr) component is in a trace amount and thus is not taken into account. The proportion (volume%) of the zirconium component can be, for example, 2% or more and 5% or less when the sum of the above-described main components (alumina component and tungsten carbide component) is taken to be 100%.

[0067] (Method of manufacturing ceramic member)

[0068] Next, a method of manufacturing the ceramic member 10 will be described. In Figure 6 one example of a method of manufacturing the ceramic member 10 is shown.

[0069] First, an alumina, a tungsten carbide, and a zirconium compound, which are raw materials of the ceramic member, are prepared (step Sll). Each of the raw materials is prepared in a powder state. Specifically, an alumina (AI2O3) powder having an average particle diameter of about 0.5 μm, a tungsten carbide (WC) powder having an average particle diameter of about 0.7 μm, and a zirconia (ZrO2) powder having an average particle diameter of about 0.4 μm are used.

[0070] The average particle diameter of the zirconia powder described herein is one example. In order to make the zirconia powder more uniformly disperse at the interface between the alumina grains and the tungsten carbide grains, the zirconia powder is preferably a finer powder. Note that the average particle diameter of the powder can be measured using a laser diffraction type particle size distribution measuring device.

[0071] Next, the prepared raw materials are weighed and mixed at a prescribed ratio (step S12). The mixing ratio of the raw materials here can be determined in accordance with the ratio (e.g., volume %) of each component desired in the resulting ceramic member 10. For example, in the case where the ceramic member 10 is produced by mixing the raw material powders and then firing them, the raw material powders can be mixed in a manner such that the mixing ratio of the raw material powders is the desired volume %. The volume % of the raw material powders can be determined in accordance with the mass of the raw material powders used for mixing and the specific gravity of each raw material.

[0072] Since the raw materials hardly react with each other in the manufacturing process, the volume % of each component in the ceramic member 10 can be made to be a desired value by adjusting the volume % of the raw materials used for mixing. Note that the ratio (volume %) of each component in the produced ceramic member 10 can be determined by the above method.

[0073] Then, pre-mixing pulverization is performed (step S13). At this time, it is preferable to perform a dispersion mixing process in which only the zirconia powder is preliminarily pulverized. Specifically, the zirconia powder is preliminarily pulverized for about 40 hours using a solvent and a ball mill. Alternatively, the particles of the zirconia powder can be pulverized using a bead mill or the like.

[0074] In the process of pre-mixing pulverization, the alumina powder and the tungsten carbide powder are mixed with a solvent (e.g., ethanol or the like) while the particles of each powder are pulverized using a ball mill. The processing time here can be less than 20 hours or more than 20 hours.

[0075] Next, a slurry is obtained by mixing and pulverizing (step S14). Specifically, the preliminarily pulverized zirconia powder and a solvent (e.g., ethanol or the like) are added to the mixture in the ball mill containing the alumina powder and the tungsten carbide powder, and further mixing and pulverization are performed.

[0076] Thus, a slurry in which the particles of the alumina, the tungsten carbide, and the zirconia are dispersed can be obtained. In the present embodiment, the time during which the zirconia is added to the mixture of the alumina and the tungsten carbide and further mixing and pulverization are performed can be about 20 hours. However, this is not limiting, and in other embodiments, the time can be less than 20 hours or more than 20 hours.

[0077] Next, the slurry is dried to produce a mixed powder (step S15). As a method for obtaining a mixed powder from a slurry, for example, a method in which the slurry is dried while being heated in a water bath to remove the solvent from the slurry, and the resulting powder is sieved can be cited.

[0078] Finally, the mixed powder is sintered by hot pressing to obtain a ceramic part (step S16). In this embodiment, during hot pressing, the mixed powder is filled into a carbon mold, and the mixed powder is heated while being uniaxially pressurized. Thus, a ceramic part 10, which is a sintered body of the mixed powder, can be obtained.

[0079] The hot pressing conditions in this embodiment are as follows: The firing temperature is 1700°C or higher and 1900°C or lower (preferably 1800°C or higher and 1900°C or lower, more preferably 1850°C); the firing time is 1 hour or higher and 3 hours or lower (preferably 2 hours); the pressure is 25 MPa or higher and 35 MPa or lower (preferably 30 MPa); and the protective gas is argon (Ar). The firing temperature during firing is preferably set near the liquid phase formation temperature of alumina and zirconium oxide. This promotes the movement (diffusion) of specific elements.

[0080] A solid ceramic component 10 can be obtained by the above manufacturing method. In the ceramic component 10 manufactured by this method, a zirconium segregation layer (i.e., Zr layer 40) is formed at the grain boundaries (i.e., interfaces) between the alumina (Al2O3) grains (i.e., alumina layer 20) and the tungsten carbide (WC) grains (i.e., WC layer 30) (see reference). Figure 3 (etc.). Therefore, it can be considered that it can enhance the adhesion of the interface and enable the ceramic component 10 to exhibit high-temperature ductility.

[0081] That is, a ceramic component 10 that maintains high ductility and has a flexural strength of over 400 MPa can be obtained even at high temperatures of around 1400°C. Furthermore, the ceramic component 10 according to this embodiment can suppress the porosity ratio in the composition to a low level (e.g., less than 0.1%) even after stress is applied.

[0082] (Applications of ceramic components)

[0083] The ceramic component 10 described in this embodiment can maintain its performance even in high-temperature environments above 1400°C. Therefore, the ceramic component 10 described in this embodiment is suitable for use as a component in devices used in high-temperature environments. Specifically, applications of the ceramic component 10 include, for example, components for gas turbines, jet nozzles for artificial satellites, molds for lenses, aircraft engine components, and sealing materials.

[0084] When the ceramic component 10 is used for the above-described purposes, for example, when... Figure 1 The rectangular ceramic component 10 shown is deformed (e.g., cut, ground, polished, etc.) into a specified shape.

[0085] (Summary of implementation methods)

[0086] Compared with the conventional heat-resistant alloy member used in a high-temperature environment, the ceramic member 10 according to the present embodiment has improved heat resistance. In addition, compared with the conventional ceramic member used in a high-temperature environment, the ceramic member 10 according to the present embodiment has reduced possibility of brittle fracture, and thus has improved reliability. Due to such characteristics, the ceramic member 10 according to the present embodiment can be applied to a member of a device and a system used in a high-temperature environment such as aerospace, power generation, and the like.

[0087] In addition, the ceramic member 10 according to the present embodiment can maintain strength at the time of deformation processing, and thus can be subjected to superplastic deformation processing, joining, and has improved moldability of a complex shape and sealing property. Due to such characteristics, the ceramic member 10 according to the present embodiment can also be used as a curved lens mold and a sealing material.

[0088] As described above, the ceramic member 10 according to the present embodiment has excellent strength and ductility in a high-temperature environment, and can be expected to exert effects in various aspects such as life improvement and processability improvement.

[0089] [Example]

[0090] Hereinafter, an example of the present application will be described. Note that the present application is not limited to the following example.

[0091] In the present example, the ceramic member 10 was manufactured according to the above-described manufacturing method, and was subjected to evaluation of high-temperature ductility. In addition, as a comparative example, a ceramic member not containing the Zr layer 40 was manufactured, and was also subjected to evaluation of high-temperature ductility.

[0092] (Raw material of ceramic member)

[0093] The raw material of the ceramic member according to the example and the comparative example and the blending ratio (vol%) thereof are as follows.

[0094] <Example>

[0095] 1. Alumina (AI2O3) powder having an average particle diameter of 0.5 μm: 55%

[0096] 2. Tungsten carbide (WC) powder having an average particle diameter of 0.7 μm: 45%

[0097] 3. Zirconia (Zr02) powder having an average particle diameter of about 0.4 μm: 5% (blending ratio (vol%) when the total of the components of the above 1. and 2. as main components is 100%)

[0098] <Comparative Example>

[0099] 1. Alumina (AI2O3) powder having an average particle diameter of 0.5 μm: 55%

[0100] 2. Tungsten carbide (WC) powder having an average particle size of 0.7 μm: 45%

[0101] (Conditions of hot pressing at the time of production)

[0102] In the examples and comparative examples, the conditions of hot pressing at the time of production were as follows.

[0103] Firing temperature: 1850°C

[0104] Firing time: 2 hours

[0105] Pressure: 30 MPa

[0106] Protective gas: argon (Ar)

[0107] (Evaluation of high temperature ductility)

[0108] For the ceramic parts involved in the examples and comparative examples, a bending strength test was performed in accordance with the following method and conditions, and the high temperature ductility was evaluated.

[0109] <Method of testing bending strength>

[0110] A test piece having a full length of 35 mm, a width of 4 mm, and a thickness of 3 mm was used to measure the bending strength. The tester obtained the 3-point bending strength of each sample of the examples and comparative examples in accordance with Japanese Industrial Standard JIS R 1601 under the following conditions.

[0111] • Temperature: 1400°C

[0112] • Protective gas: argon (Ar)

[0113] • Deflection speed: 0.5 mm / min

[0114] • Bending span: 30 mm

[0115] • Testing machine: MST808 type ultra-high temperature material testing machine

[0116] • Gripper material: SiC

[0117] <Results>

[0118] For the ceramic parts involved in the examples, it was confirmed that the bending strength exceeded 400 MPa under temperature conditions of 1400°C. In contrast, for the ceramic parts involved in the comparative examples, it was confirmed that fracture occurred when a bending stress of about 300 MPa was applied under temperature conditions of 1400°C.

[0119] (HAADF-STEM image of the ceramic part)

[0120] An HAADF-STEM image of one cross section of the ceramic part involved in the present example before the bending test is shown in Figure 3.like Figure 3 As shown, an atomic layer formed by zirconium (Zr) was confirmed to exist at the grain boundary between the alumina (Al2O3) grains and the tungsten carbide (WC) grains. Furthermore, it was confirmed that the atomic layer formed by zirconium was formed with a thickness of 1 arrangement on the (100) face of the tungsten carbide (WC) grains.

[0121] It should be noted that in the ceramic components involved in the comparative examples, it was confirmed that no zirconium atomic layers were formed at the grain boundaries.

[0122] (TEM image of the ceramic component)

[0123] A TEM image of a cross-section of the ceramic component involved in this embodiment before the bending test is shown. Figure 2 Additionally, a TEM image of a cross-section of the ceramic component involved in this embodiment after a bending test is shown below. Figure 5 . Figure 5 The TEM image shown is in conjunction with Figure 2 The TEM images shown are obtained by preparing the sample and observing the sample using the same method.

[0124] like Figure 2 As shown, it was confirmed that the ceramic component had almost no porosity in its microstructure before the bending test. Furthermore, after the bending test, it was confirmed that the microstructure of the ceramic component contained... Figure 5 The area indicated by the middle arrow will produce several pores (cavities).

[0125] (Porosity of ceramic components)

[0126] The results of the porosity measurement in a cross-section of the ceramic component involved in this embodiment before the bending test are shown below. Figure 4 .

[0127] like Figure 4 As shown, in the ceramic component involved in this embodiment, it was confirmed that the porosity ratio in the three extracted samples (samples 1 to 3) was less than 0.3%.

[0128] (Summary of Examples)

[0129] Based on the above results, it has been confirmed that the ceramic component involved in this embodiment has ductility (the property of not undergoing brittle fracture) even in ultra-high temperature environments above 1400°C, and can maintain a high bending strength of over 400 MPa.

[0130] The embodiments disclosed this time should be considered illustrative in all points and not restrictive. The scope of the present application is shown by the claims rather than the above description, and it is intended to include all modifications within the meaning and scope equivalent to the claims. In addition, structures obtained by combining the structures of the different embodiments explained in this specification are also included in the scope of the present application.

[0131] Explanation of Reference Signs

[0132] 10: Ceramic member

[0133] 20: Alumina layer (grains of alumina)

[0134] 30: WC layer (grains of tungsten carbide)

[0135] 40: Zr layer (atomic layer formed of zirconium)

Claims

1. A ceramic component comprising alumina (Al₂O₃) and tungsten carbide (WC), An atomic layer of zirconium (Zr) exists at the grain boundaries between the alumina (Al2O3) grains and the tungsten carbide (WC) grains. The porosity of any cross-section of the ceramic component is less than 0.3%.

2. The ceramic component according to claim 1, wherein, The atomic layer is formed at the grain boundary according to the arrangement period of at least one of the alumina (Al2O3) grains and the tungsten carbide (WC) grains.

3. The ceramic component according to claim 2, wherein, The atomic layers are formed at the grain boundaries according to the arrangement period of the (100) face of the tungsten carbide (WC) grains.

4. The ceramic component according to claim 3, wherein, The atomic layer is formed at the grain boundary with a thickness of 1 arrangement of the (100) face of the tungsten carbide (WC) grain.

5. The ceramic component according to any one of claims 1 to 4, which is used in a high-temperature environment above 1400°C.

6. The ceramic component according to any one of claims 1 to 4, used in any one of gas turbine components, satellite jet nozzles, lens molds, aircraft engine components, and sealing materials.

Citation Information

Patent Citations

  • On-vehicle CD player

    JP1989091363A